Imidazolium chloride immobilized on copper acetylacetonate-grafted magnetic chitosan as a new metal/ionic liquid bifunctional catalyst for selective oxidation of benzyl alcohols in water. Issue 92 (20th September 2016) - Azizi, Kobra; Esfandiary, Naghmeh; Karimi, Meghdad; Yazdani, Elahe; Heydari, Akbar
Abstract : Copper acetylacetonate and 1-methyl-3-propyl imidazolium chloride immobilized on chitosan magnetic nanoparticles via covalent attachment as dual metal–ionic liquid catalyst for selective oxidation of benzyl alcohols under mild and co-catalyst free conditions. Abstract : Copper acetylacetonate and 1-methyl-3-propylimidazolium chloride as an ionic liquid (Fe3 O4 /CS/Cu/IL) were immobilized on chitosan magnetite nanoparticles via covalent attachment. The prepared heterogeneous catalyst was characterized by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), X-ray powder detection (XRD), thermogravimetric/differential thermal analyses (TG/DTA), vibrating sample magnetometry (VSM), inductively coupled plasma atomic emission spectroscopy (ICP-AES) and energy dispersive X-ray (EDX) spectroscopy. The Fe3 O4 /CS/Cu/IL exhibits superior catalytic activity for the oxidation of various benzyl alcohols to the corresponding carboxylic acids using TBHP as an oxidant. The catalyst could be simply recycled with the assistance of an external magnet and reused for five runs without significant loss of activity.